PENDERITAAN SEBAGAI PENYELAMATAN STUDI KOMPARASI ANTARA PENDERITAAN YESUS KRISTUS DENGAN PENDERITAAN IMAM HUSAYN - Ismoyo, Thomas Ulun (Jurnal Teologi (Journal of Theology), 2012)
The theological concepts of suffering and redemption as developed in Christianity have echoed in a certain manner in the Shiites Islam. This is clear from the martyrdom of imam Husayn in Karbala. The suffering and death of Imam Husayn, for the Shiites, offer the desire to take participation in it for their salvation in the hereafter. The participation in expressed in some rituals, like taziyah and ziyarah. As for in Christianity , especially in Catholicism, the memory of the suffering and death of Jesus Christ is expressed in some prayers and devotions, one of which is the Stations of the Cross. Apart from the parallelism, there are also some dissimilarities on the significance of suffering as well as redemption in the Shiite and Catholicism theologies.